7 Transoral Laser Microsurgery for Intermediate Supraglottic Cancer (Laryngeal Cancer, 2019)
Locally intermediate supraglottic squamous cell carcinoma (SCCs) may be managed by a variety of surgical and nonsurgical approaches. First, when planning transoral laser microsurgery (TLM), the surgeon should fully delineate superficial and deep tumor infiltration. This may be done by careful endoscopic examination (using both white light and narrowband imaging) and cross-sectional imaging (CT and/or MR). Furthermore, nodal involvement should be routinely assessed (ideally by ultrasonography) in order to get a comprehensive view of the extension of the disease. TLM resection of each supraglottic subsite is characterized by different outcomes in terms of survival and function. While the quality of the voice is usually not influenced, a varied degree of swallowing impairment and aspiration should be expected temporarily. In general, patient evaluation has a crucial role in determining the optimal treatment and should be aimed at balancing oncologic and functional outcomes. For this reason, when assessing the “ideal” treatment for a given clinical scenario, it is mandatory to tailor the therapeutic choice in consideration of both patient- and tumor-related factors. The main limiting factors influencing the treatment choice when considering TLM in locally intermediate supraglottic carcinomas will be presented and discussed in the text, with particular emphasis on preoperative evaluation and planning.
Keywords: laryngeal cancer; supraglottic carcinoma; transoral laser microsurgery; supraglottic laryngectomy; survival; functional outcomes